Impacts and Lessons Learnt From Local Production of WHO Recommended Alcohol Based Hand Rub During Covid-19 Pandemic in Uganda - Tusabe, Fred; Otita, Morgan; Kesande, Maureen; Twinomugisha, Fred (Research Square, 2020)
The Government of Uganda through the Ministry of Health and other partners have promoted hand washing and hand rubbing using ABHS as one of the key preventive measures against person-to-person spread of the Covid-19 virus. The people of Uganda have greatly heeded to these messages and as a result, the demand for ABHS has increased because of high consumption rates. A district multi modal design was established in 2019 in Kabarole and Kasese districts in Western Uganda Part of the strategy was to set up an ABHS production units. The prevailing COVID-19 outbreak has instigated set up at centrally located Kasangati HCIV. We analysed the demand and production of ABHS produced before and during the COVID-19 outbreak.
Keywords: COVID-19, Hand sanitizer, Hand hygiene, Infectious diseases, Uganda